Integrated analysis of lncRNA-mediated ceRNA network involved in immune regulation in the spleen of Meishan piglets - Shi, Jing; Xu, Chao; Wu, Zhengchang; Bao, Wenbin; Wu, Shenglong (Frontiers in Veterinary Science, 2022)
Meishan pig is a famous local pig breed in China, with high fertility and strong immunity. The spleen is the largest lymphoid organ in pigs and performs essential functions such as immunity and hematopoiesis. The invasion of many pathogenic microorganisms in pigs is associated with spleen damage, and long non-coding RNAs (lncRNAs) has been demonstrated to be associated with splenic immune regulation. However, the expression network of mRNAs and lncRNAs in the spleen of Meishan pigs remains unclear. This study collected spleen tissues from Meishan piglets at three different days of age as a model, and mRNA and lncRNA transcripts were profiled for each sample. Additionally, 1806 differential mRNAs and 319 differential lncRNAs were identified. A complicated interaction between mRNAs and lncRNAs was identified via WGCNA, demonstrating that lncRNAs are a crucial regulatory component in mRNA. The results showed that the red and black modules at 28 days of age have similar mRNA and lncRNA transcription patterns and are mainly involved in the immune defense response process. These two modules of mRNAs and lncRNAs were mapped by predicted miRNAs to ceRNA networks and screened to the core splenic tissue genes (IFIT1, DHX58) and key lncRNAs (TCONS-00002102, TCONS-00012474) in the Meishan piglet. The expression of these genes is related to the immune response of pigs. These findings contribute to a further understanding of mRNA and lncRNA expression in the spleen of piglets, and provide new ideas to improve the disease resistance of piglets.